PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS UNTUK MENINGKATKAN SIKAP SISWA TERHADAP SAINS DI KELAS VII MTS AL-HUDA PEKANBARU - Kartini Usja; M. Rahmad '; M.Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This reasearch aimed to determine students' attitudes on science by applying cooperative learning model talking chips at junior high school science learning on Objects Classification matter. The subject of this research was the students of class VII C Mts Al-Huda Pekanbaru, that consisted of 26 students. The data of this reasearch was primary data obtained  from students’ prestest and post-test scores using students' attitudes questionnaire on science and then analyzed descriptively. It consisted of four indicators, they were interesting in science, science learning activities, the importance of science and views on science  environmental. Based on data analysis with Likert scale questionnaire obtained an average of 1-4 students' attitudes toward sians with initial score of 2.58 and a final score of 2.83 was obtained high category.   And then  students' attitudes increasing on science was analyzed by using a gain an obtained score 0.17 by low category. There for it  can concluded Aplication Cooperative Learning Model Type Talking Chips can improve students' attitudes on science in class VIIC Mts Al-Huda Pekanbaru with low gain category.